Successful reproductive outcome after laparoscopic Strassmann's metroplasty - S.D.S. Karthik; Alka Kriplani; Reeta Mahey; Garima Kachhawa (Wolters Kluwer Medknow Publications, 2017)
Mullerian anomalies cause a significant impact on the reproductive outcomes. A bicornuate uterus is a type of lateral fusion defect, which constitutes 26% of all uterine anomalies. Strassmann's metroplasty is a unification procedure performed to correct the two smaller uterine cavities into a more spacious single cavity. Improved reproductive performance was reported after unification metroplasty. Laparoscopic route can be adopted for this procedure with all the advantages of minimally invasive surgery. Here, we report a success story of a woman who suffered with six miscarriages and secondary infertility who underwent laparoscopic Strassmann's metroplasty in a tertiary care center and later delivered a baby by caesarean section.